Acute generalized exanthematous pustulosis in a patient after stem cell transplantation - Cetkovská, Petra; Benáková, Nina (Journal of cutaneous medicine and surgery, 2010)
BACKGROUND: a severe generalized pustular eruption occurred several months after allogeneic hematopoietic stem cell transplantation for multiple myeloma in a patient being treated with antibiotics for respiratory infection. Neither he nor his donor had a history of psoriasis. METHODS: the patient was treated with drug withdrawal and administration of cyclosporine and methylprednisolone without improvement; later, acitretin and methylprednisolone were used successfully. The eruption slowly subsided, and therapy was discontinued. Four months later, the patient experienced a recurrent severe pustular eruption associated with fever and leukocytosis, and the same treatment was used successfully again. RESULTS AND CONCLUSION: the patient has not experienced relapses in the ensuing 3 years. Acute generalized exanthematous pustulosis is a rare cutaneous adverse reaction triggered most commonly by drugs with a tendency to resolve spontaneously. The surprisingly prolonged, refractory, and relapsing course of the eruption in our patient might be due to the immune alteration and the polypharmacologic therapy after stem cell transplantation.
Keywords: recidiva; transplantace hematopoetických kmenových buněk; Humans; antiflogistika; lidé středního věku; Hematopoietic Stem Cell Transplantation; Multiple Myeloma; kůže; lidé; akutní generalizovaná exantematózní pustulóza; acitretin; mnohočetný myelom; Acute Generalized Exanthematous Pustulosis; Postoperative Complications; pooperační komplikace; methylprednisolon; Male; Middle Aged; Keratolytic Agents; Methylprednisolone; Recurrence; Anti-Inflammatory Agents; mužské pohlaví; Acitretin; keratolytika; kombinovaná farmakoterapie; Skin; Drug Therapy, Combination